Final paper: AR 592 Seminar - McBroom, Kenny, author (Colorado State University. Libraries, 2008)
Though it can be assumed that any artist living at any time goes through some sort of stylistic change, one can always see art historical influences, to some degree, in their work. My recent themes have included pseudo-criticisms/commentaries on technology, art, and art school. Drawing influence from horror movies, television commercials, comic books, cartoons, philosophy, war, art history and so on, my works attempt to create a combination of a high/low art relationship and present the arrangement in an aesthetically successful way. My own work is currently at the beginning of a change in approach, regarding appearance, though I will attempt to give a fair assessment to prior works. The future pieces will still have a strong conceptual link to everything described in this paper.
May 14, 2008.